Principles of Entrepreneurship (ENT530): Social Media Portfolio: Smiley Penny / Khairi Azim Mohd Fadir - Mohd Fadir, Khairi Azim (2021)
This project is one of the business established for subject that I am studying in semester 4 which is related to entrepreneurship. This business I introduce is Smiley Penny. My online businesses are commonly more focused on quantities and qualities. Smiley Penny is an online business run by Khairi Azim bin Mohd Fadir. The address at No 531, Jalan A18, Vila Suria / Taman Warisan Puteri, 70400 Seremban, Negeri Sembilan Darul Khusus. Smiley Penny offer the best for our customer. Our target market is individual from all range of ages who loves plushies or stuffed animal toys with softness, cuteness, and affordable price. We do not target any specific area because we sell it online. Smiley Penny provides self-pickup services and cash on delivery services (COD) for the customers living in Seremban, Negeri Sembilan. For the customers outside Seremban, the customers will receive their plushies through postage from J&T Express. Our plushies will package in a box with protective packaging to ensure the plushies will not damage and provide satisfactory to our customer. Because of our ambition to preserve the environment, our packaging can be reused and recycled. In our business, we are more focused on giving the highest quality of plushies to the customers. This is because we are aware that customer satisfaction plays an important role in the business. Thus, we offer our plushies that made entirely with love and care to ‘Bring Smile To Everyone’. Finally, I hope Smiley Penny online business that I am doing is accepted to the public and will progress in the future. In regard, I am very grateful for the opportunity given to start my business online and happy with our customer being satisfied with plushies they received.